MEREKONSTRUKSI GERAKAN DAKWAH MASA DEPAN - M.Yusuf Asry (Harmoni, 2012)
The Islamic Dakwah needs to apply appropriate methods so it is well orientated and in line with its objectives, it is conveying religious messages. At the beginning of the 20th century in Indonesia had started appearing several social-religious organizations that apply the principles of modern organizations, such as the Syarikat Dagang Islam (SDI), Islam SI (SI), followed by Persyarikatan Muhammadiyah and NU. In general, these organizations deliver four ideas that become the spirit and ideology, which are: religion, sociology, education and economy. The development of the community-based Islamic da’wah management was understood to be implemented as new measures to facilitate the community in order to formulate the principles of the missionary program, by and for the community itself.